BILATERAL OCCIPITAL POLE HYPERTENSIVE STROKE DIAGNOSED WITH MACULAR INTEGRITY ASSESSMENT (MAIA) MICROPERIMETRY. (2017) - Kasi, Sundeep K.; Shahlaee, Abtin; Adam, Murtaza K.; Ehmann, David S.; Sivalingam, Arunan
Abstract : Purpose: To describe the utility of microperimetry testing in the diagnosis of a bilateral occipital stroke. Methods: Retrospective case report. Results: A 57-year-old male with hypertension presented with complaints of bilateral blurred central vision and bilateral hypertensive retinopathy with cotton-wool spots. Automated perimetry demonstrated a central scotoma in both eyes that did not respect the vertical midline; however, microperimetry testing revealed a bilateral homonymous hemianopia that suggested cerebrovascular disease which was subsequently confirmed with magnetic resonance imaging. Discussion: In cases of unexplained central visual loss, microperimetry testing may be a useful ancillary test for the diagnosis of cerebrovascular disease. Abstract : The authors report a case of a bilateral occipital pole stroke causing central vision loss with homonymous changes detected with microperimetry. In cases of unexplained central vision loss, microperimetry testing may be helpful in the diagnosis of cerebrovascular disease because of its increased sensitivity for detection of subtle changes suggestive of a homonymous hemianopia.